Perspektif Pendiri dan Respons Masyarakat Dalam Pendirian Sekolah Islam Terpadu - Ifnaldi Ifnaldi (Belajea: Jurnal Pendidikan Islam, 2022)
Rejang Lebong Regency is the oldest district in Bengkulu Province. In 1967 before splitting using the South Sumatra Province, Rejang Lebong Regency as the center of government. Curup as the capital of the district is known for using good manners, polite manners, and the people who are religious and identified by the community as using a religious education city. The perspective of establishing an Islamic school has pillars as its basis, including: (1) Islamic education services; (2) activating Islamic da'wah; (3) empowering the younger generation; (4) maintaining belief based on the threat of apostasy, and; (5) maintaining the ideology of the sect/organization. The method used in this research is descriptive qualitative. Research is conducted based on facts or phenomena that exist empirically in life and life. This research was conducted at the Rabby Rabiyah Integrated Islamic Elementary School, an Al-Islah Curup Education Foundation. This data collection was carried out for 2 months in Telpel Rejo Village, Curup Tengah District, Rejang Lebong Regency. The data sources were in the form of recordings of conversations and notes from observations. Data Collection Techniques Researchers are the key instruments that go directly to the field to collect data. While complementary instruments in the form of cassettes, tape recorders, and other writing instruments. The techniques used are tapping/observing techniques, engaging listening techniques, recording techniques, and note-taking techniques. Data were collected for approximately 2 months in various ways, namely taking notes, interviewing and recording. The data analysis technique used is inductive and deductive techniques. This means that after the data is collected, the data must first be adjusted to the existing theory. Furthermore, from the theory back to the data and facts found. The suitability of data and theory can strengthen existing theories but can also produce new theories. i.